Manajemen Rekrutmen Guru Di Sekolah : Studi Literatur - Annissa Fitriani Rizka; Benediktus Rahawarin; Yosi Kristiyana; Unifah Rosyidi; Muh. Takdir (Departement of Mathematics Education, 2025)
One of the biggest factors to enhance the quality of education in Indonesia is the educators themselves. The educator or teacher plays a big part in the process of education, which makes the process of recruiting teachers very important. This research aims to find the meaning of recruitment management in school, the process, the strategy, and the challenge of the recruitment process. Using collective works of literatures to study, this research uses the qualitative method approach. Based on the literature, it is concluded that recruitment management in school is a process that starts from planning the process until the placement of the candidates (teachers). There are a lot of strategies and challenges depending on the location of the school. It makes the recruitment management vary based on the location of the school.